Manipulative Influence in the Spanish Political Discourse: Words Stereotypes, Words Symbols and Words Slogans - K. V. Kucherenko (Vestnik MGIMO-Universiteta)
The article is devoted to a problem of manipulative influence in the Spanish political discourse. The article gives the characteristic of manipulative influence as the important function of a political discourse. One of tactics of manipulative influence are words stereotypes, words symbols and words slogans. In the article is found out the specific character of manipulative influence which used by the politicians of all persuasions.